A Guide for Understanding, Publishing, and Building a Career in Entrepreneurship Education. (2nd July 2022) - Weaver, K. Mark; Edwards, Chase J.; Solomon, Shelby J.; Bendickson, Joshua S.
The following manuscript is a helpful overview for current and aspiring academics that seek to better understand academic research, the publishing process, and building a career in entrepreneurship education. We draw from management literature given the theoretical and practical similarities, and we provide suggestions to entrepreneurship educators as a means of starting a dialogue as opposed to presenting fact. While this guide is not directed toward experienced scholars, it may serve as a helpful review. Publishing in entrepreneurship journals is a worthwhile scholarly endeavor for researchers in a variety of fields and we hope our efforts are helpful to scholars, authors, and entrepreneurship educators.